Factores Biosocioculturales y Nivel de Conocimiento materno Sobre Enfermedades Diarreicas Agudas en Menores de 5 años, Centro de Salud Materno "Santa Catalina" San Pedro de LLoc - Briones Vasquez, Sandra Fabiola (2013)
This qualitative study, descriptive - exploratory study was conducted in the city of Trujillo, with the aim of describing and analyzing the different responsibilities that the nurse required to work in the new workspace, in order to strengthen knowledge Nursing embodied in the new workspaces. The information was obtained through open an interview which was applied to four nurses who work in the new areas of work: NGOs, youth center, mining and agribusiness center. The speeches were analyzed emerging three core competencies: personal, emotional and social, within which are present sub-categories such as: be tolerant, creative and innovative, to provide humanistic care, have the capacity for selftransformation, be empathetic and self -creative, working with delivery based on community work and as a team, being an educator and communicator and have knowledge of occupational health, which allow us to show that not having enough skills but that the nurse needs to function efficiently in other new workspaces. Keys words: professional competence - new work spaces